Barium titanate powder, its manufacturing method, and filler for sealing material

The method of high-temperature formation, firing, and cleaning of barium titanate particles addresses impurity issues, resulting in high-purity powder with enhanced dielectric properties for improved electronic component performance.

JP7606596B2Active Publication Date: 2024-12-25DENKA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023508858
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-22
Filing Date
2022-02-28
Publication Date
2024-12-25
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

Barium titanate powders used as fillers in electronic components contain impurities, particularly barium ions, which cause corrosion and reduce the reliability and hardenability of encapsulants, and existing methods struggle to achieve high purity levels efficiently.

Method used

A manufacturing method involving high-temperature formation, firing, and aqueous cleaning of barium titanate particles, followed by classification to achieve high purity and improved dielectric properties.

Benefits of technology

The method produces barium titanate powder with high purity and dielectric constant, reduced impurities, and improved sphericity, enhancing the reliability and performance of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606596000001
    Figure 0007606596000001
Patent Text Reader

Abstract

A production method for a barium titanate powder, said method comprising: a step (a) in which a starting material that contains a barium titanate compound is sprayed in a high-temperature site heated to a temperature equal to or greater than the melting point of the compound to form a barium titanate particles; a step (b) in which a powder containing the barium titanate particles formed in step (a) is fired; and a step (c) in which the fired product obtained in step (b) is cleaned with a water-based cleaning solution.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a barium titanate powder, a method for producing the same, and a filler for an encapsulant. [Background technology]

[0002] Barium titanate compounds are known as materials with extremely high relative dielectric constants, and are widely used as fillers in various electronic component materials (eg, sealing materials) that require high dielectric constants.

[0003] However, the barium titanate powder used as the filler is prone to containing impurities that are generated during the manufacturing process, and if such impurities are eluted, there is a problem that the electrical characteristics and long-term reliability of the electronic component material are reduced.

[0004] Therefore, Patent Document 1 proposes a method for producing barium titanate powder with a low impurity content by controlling the pH of the titanium compound, the chlorine content of the titanium compound, and / or the concentrations of the titanium compound and the barium compound when producing barium titanate powder by hydrothermal synthesis using a titanium compound and a barium compound. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-261912 A Summary of the Invention [Problem to be solved by the invention]

[0006] It has been confirmed that ionic impurities mixed into barium titanate powder during the manufacturing process reduce the hardening properties of sealing materials, etc., and that, among the substances that dissolve, barium ions are likely to cause corrosion of Cu wiring and reduce the reliability of the sealing material. In this regard, it is difficult to reduce the amount of ionic impurities (especially barium ions) dissolved by the method of Patent Document 1. In addition, although it is possible to partially remove ionic impurities by washing the barium titanate powder (for example, by washing with water), it is difficult to achieve a certain level of purity, and further, the need to repeat washing several tens of times causes a decrease in production efficiency.

[0007] Therefore, a main object of the present invention is to provide a barium titanate powder with higher purity and a method for producing the same. [Means for solving the problem]

[0008] One aspect of the present invention provides a method for producing a barium titanate-based powder, the method comprising: step a) of forming barium titanate-based particles by injecting a raw material containing a barium titanate-based compound into a high-temperature field heated to a temperature equal to or higher than the melting point of the compound; step b) of firing the powder containing the barium titanate-based particles formed in step a; and step c) of washing the fired product obtained in step b with an aqueous cleaning liquid.

[0009] According to the manufacturing method of the above aspect, a barium titanate powder with higher purity can be obtained. Furthermore, according to the manufacturing method of the above aspect, it is not necessary to repeat washing several tens of times, and production efficiency can be improved.

[0010] In one embodiment, the method for producing a barium titanate powder may further include a step d of classifying the powder containing barium titanate particles formed in the step a to obtain a plurality of powders having different average particle sizes. In this case, in the step b, among the plurality of powders obtained in the step d, the powder having an average particle size of 5.0 μm or less and a true specific gravity of 5.60 to 5.90 g / cm is selected. 3 may be used as the powder containing barium titanate-based particles formed in step a.

[0011] Another aspect of the present invention provides a powder containing barium titanate particles, the barium ion concentration being 500 mass ppm or less, and when 30 g of the powder is mixed with 142.5 mL of ion-exchanged water having an electrical conductivity of 1 μS / cm or less and 7.5 mL of ethanol having a purity of 99.5% or more, the mixture is shaken for 10 minutes, and then allowed to stand for 30 minutes to prepare an extract, the extract has an electrical conductivity of 200 μS / cm or less.

[0012] In one embodiment, the barium titanate powder may have a relative dielectric constant of 100 to 310 at 1 GHz.

[0013] In one embodiment, the barium titanate powder may have an average particle size of 3.0 to 7.0 μm.

[0014] In one embodiment, the barium titanate based powder may have an average sphericity of 0.80 or greater.

[0015] Another aspect of the present invention provides a filler for an encapsulant, comprising the barium titanate powder of the above aspect. Effect of the Invention

[0016] According to the present invention, it is possible to provide a barium titanate powder having a higher purity and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] In this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In addition, unless specifically stated otherwise, the units of the numerical values ​​described before and after "~" are the same. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range may be replaced with the upper limit or lower limit of a numerical range of another stage. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In addition, the upper limit and lower limit values ​​described individually can be combined arbitrarily.

[0018] Preferred embodiments of the present invention will be described below, however, the present invention is not limited to the following embodiments.

[0019] A method for producing a barium titanate-based powder in one embodiment includes step a of forming barium titanate-based particles by injecting a raw material containing a barium titanate-based compound into a high-temperature field heated to a temperature equal to or higher than the melting point of the compound, step b of firing the powder containing the barium titanate-based particles formed in step a, and step c of washing the fired product obtained in step b with an aqueous cleaning liquid.

[0020] The above method can also be described as a method for removing ionic impurities (particularly barium ions) from barium titanate-based powder. In the above method, by carrying out step b after step a, the washing effect in step c can be improved. Therefore, according to the above method, ionic impurities (particularly barium ions) from barium titanate-based powder can be efficiently removed with fewer washings, making it possible to obtain barium titanate-based powder with higher purity.

[0021] Furthermore, as a result of the investigations by the present inventors, it has become clear that in the above-mentioned method, the relative dielectric constant of the barium titanate-based powder is improved by carrying out step b. Therefore, according to the above-mentioned method, it is possible to obtain a barium titanate-based powder having high purity and a high relative dielectric constant.

[0022] Moreover, the above method can further improve the sphericity and tetragonal ratio, that is, the above method can provide a barium titanate powder having an average sphericity close to 1 and a tetragonal ratio close to 100%.

[0023] The method may further include a step d of classifying the powder containing barium titanate particles formed in the step a to obtain a plurality of powders having different average particle sizes. This step d may be performed after the step a and before the step b, or may be performed simultaneously with the step a.

[0024] Hereinafter, each step (step a, step b, step c, and step d) in the method for producing a barium titanate powder will be described.

[0025] <Process a> In step a, a raw material containing a barium titanate-based compound is injected into a high-temperature field to melt and solidify the raw material, thereby forming barium titanate-based particles with high sphericity.

[0026] The raw material is a solid (e.g., particles) containing a barium titanate-based compound. In general, perovskite oxides such as barium titanate have an ABO3 crystal structure. Both the A site and the B site are easily substituted with other elements, and it is possible to substitute different elements such as Nd, La, Ca, Sr, and Zr into the crystal structure. In this specification, in addition to barium titanate, compounds in which different elements are substituted on the A site and / or B site of barium titanate are collectively referred to as barium titanate-based compounds. Examples of barium titanate-based compounds include compounds represented by the following formula (1) and compounds represented by the following formula (2). (Ba (1-x) Ca x )(Ti (1-y) Zr y )O3…(1) [In formula (1), x and y satisfy 0≦x+y≦0.4.] La x Ba (1-x) Ti (1-x / 4) O3…(2) [In formula (2), x satisfies 0 < x < 0.14.]

[0027] The shape of the raw material is not particularly limited and may be regular or irregular. The raw material may contain components other than the barium titanate-based compound (for example, components such as unavoidably contained impurities). The content of the barium titanate-based compound in the raw material may be 98 to 100% by mass, or may be 99 to 100% by mass, based on the total mass of the raw material.

[0028] The average particle size of the raw material may be 0.5 to 3.0 μm, or may be 1.0 to 2.5 μm or 1.5 to 2.0 μm. The larger the average particle size of the raw material, the larger the average particle size of the barium titanate-based particles obtained in step a, and the smaller the average particle size of the raw material, the smaller the average particle size of the barium titanate-based particles obtained in step a. When the average particle size of the raw material is within the above range, barium titanate-based particles with an average particle size of 3.0 to 7.0 μm are likely to be obtained in step a. In this specification, the average particle size is the particle size (D50) at which the cumulative mass is 50% in the particle size distribution obtained by mass-based particle size measurement by the laser diffraction light scattering method, and can be measured using "Mastersizer 3000, wet dispersion unit: Hydro MV attached" manufactured by Malvern.

[0029] In step a, the raw material may be mixed with a solvent to form a slurry before use. That is, in step a, a slurry containing the raw material and the solvent may be injected into a high-temperature field. When injecting the slurry, the sphericity of the barium titanate-based particles is likely to be improved due to the surface tension of the solvent.

[0030] As the solvent, for example, water is used. As the solvent, organic solvents such as methanol and ethanol can also be used for the purpose of adjusting the calorific value. These may be used alone or in combination.

[0031] From the viewpoint of facilitating increasing the sphericity of the barium titanate particles, the concentration (content) of the raw material in the slurry may be 1 to 50 mass%, 20 to 47 mass%, or 40 to 45 mass% based on the total mass of the slurry.

[0032] The high-temperature field may be, for example, a high-temperature flame formed in a combustion furnace or the like. The high-temperature flame can be formed by a combustible gas and a combustion supporting gas. The temperature of the high-temperature field (for example, the high-temperature flame) is a temperature equal to or higher than the melting point of the barium titanate compound used as the raw material, for example, 1625 to 2000°C.

[0033] Examples of the flammable gas include propane, butane, propylene, acetylene, and hydrogen. These gases can be used alone or in combination of two or more. Examples of the combustion supporting gas include oxygen-containing gases such as oxygen gas. However, the flammable gas and the combustion supporting gas are not limited to these.

[0034] The injection (spray) of the raw material can be carried out, for example, using a two-fluid nozzle. The injection speed (feed rate) of the raw material may be 0.3 to 32 kg / h, or 9 to 29 kg / h, or 22 to 27 kg / h. When the injection speed of the raw material is within the above range, the sphericity of the barium titanate particles is likely to be improved. When a slurry is used, the injection speed of the raw material in the slurry may be within the above range.

[0035] A dispersion gas may be used when injecting the raw material. That is, the raw material (or a slurry containing the raw material) may be injected while being dispersed in the dispersion gas. This makes it easier to improve the sphericity of the barium titanate particles. As the dispersion gas, a combustion-supporting gas such as air or oxygen, or an inert gas such as nitrogen or argon can be used. A combustible gas can also be mixed into the inert gas in order to adjust the calorific value of the gas. The supply speed of the dispersion gas is set to 20 to 50 m / s from the viewpoint of facilitating the increase in the sphericity of the barium titanate particles. 3 / h, 30 to 47 m 3 / h or 40~45m3 / h may also be used.

[0036] The barium titanate particles formed in the above step a may contain components other than the barium titanate compound (for example, components such as unavoidably contained impurities). The content of the barium titanate compound in the barium titanate particles may be 98 to 100 mass % or may be 99 to 100 mass % based on the total mass of the barium titanate particles.

[0037] The average sphericity of the barium titanate particles formed in the above step a (average sphericity of the powder containing barium titanate particles) is, for example, more than 0.70. In the above step a, barium titanate particles having an average sphericity of 0.80 or more or 0.85 or more can be obtained by adjusting the injection speed of the raw material, using a slurry, using a dispersion gas, etc. In addition, when performing the step d described below, it is also possible to further increase the sphericity by classification. The maximum value of the average sphericity is 1.

[0038] In this specification, the average sphericity means a value measured by the following method. First, a sample powder is mixed with ethanol to prepare a slurry with a concentration of the sample powder of 1% by mass, and the slurry is dispersed for 2 minutes at output level 8 using a Branson "SONIFIER450 (crushing horn 3 / 4" solid type). The obtained dispersed slurry is dropped onto a sample stage coated with carbon paste using a dropper. The dropped slurry is left to stand in the air on the sample stage until it dries, and then osmium coating is performed, and the resultant is photographed using a JEOL Ltd. scanning electron microscope "JSM-6301F type". The photograph is taken at a magnification of 3000 times to obtain an image with a resolution of 2048 x 1536 pixels. The obtained image is imported into a photographing computer, and the particles are recognized using an easy import tool using an image analyzer "MacView Ver. 4" manufactured by Mountec Co., Ltd., and the sphericity is measured from the particle's projected area (A) and perimeter (PM). If the area of ​​a perfect circle corresponding to the perimeter (PM) is (B), then the sphericity of the particle is A / B. If we assume a perfect circle (radius r) with the same perimeter as the perimeter (PM) of the sample, PM=2πr, B=πr2 Therefore, B = π × (PM / 2π) 2 The sphericity (A / B) of each particle is A×4π / (PM) 2 The sphericity of 200 particles having an equivalent circle diameter of 2 μm or more in any projected area thus obtained is calculated, and the arithmetic mean value is taken as the average sphericity.

[0039] <Process d> In step d, the powder containing barium titanate particles formed in step a is classified. The classification method is not particularly limited, and may be screen classification or wind classification. From the viewpoint of efficient classification, it is preferable to directly connect a collection line to the bottom of the combustion furnace in which step a is performed, and classify the powder containing barium titanate particles by sucking the barium titanate particles in the combustion furnace through the collection line using a blower installed behind the collection line (opposite the combustion furnace). The collection line may have a cyclone and a bag filter in addition to a heat exchanger connected to the combustion furnace. The heat exchanger, cyclone, and bag filter may be connected in series in this order. In this case, the powder containing barium titanate particles is collected in each of the combustion furnace, the heat exchanger, the cyclone, and the bag filter. The particle size of each powder collected can be adjusted, for example, by the amount of suction of the blower.

[0040] When the above-mentioned collection line is used in step d, the powder collected on the upstream side (closer to the combustion furnace) tends to have a true specific gravity closer to that of the barium titanate compound. This is presumably because the collected powder is more likely to contain impurities with low specific gravity (such as barium carbonate) on the downstream side (closer to the blower). In addition, when the above-mentioned collection line is used in step d, the powder collected by the cyclone tends to have the highest sphericity.

[0041] In step d, the powder containing barium titanate particles may be classified so that at least one of the obtained powders has an average particle size of 5.0 μm or less. By using a powder having the above average particle size in step b, the cleaning effect in step c tends to be improved, and the relative dielectric constant of the barium titanate powder tends to be improved. The average particle size of the powder may be 3.0 to 5.0 μm, 3.2 to 4.8 μm, or 3.5 to 4.5 μm.

[0042] <Process b> In step b, the powder containing the barium titanate particles formed in step a is fired to obtain a fired product of the powder.

[0043] As the powder containing barium titanate particles formed in step a, one of a plurality of powders obtained by classifying the powder containing barium titanate particles formed in step a may be used. That is, in step b, one of the powders obtained in step d may be used. When the above-mentioned collection line is used in step d, the cleaning effect in step c tends to be improved by using the powder collected by a cyclone, and the relative dielectric constant of the barium titanate powder tends to be improved.

[0044] The average particle size of the powder used in step b may be 5.0 μm or less, 4.5 μm or less, or 4.0 μm or less, from the viewpoint of more easily improving the cleaning effect in step c and more easily improving the relative dielectric constant of the barium titanate powder. The average particle size of the powder used in step b may be 2.0 μm or more, from the viewpoint of preventing aggregation and adhesion between particles during firing. From these viewpoints, the average particle size of the powder used in step b may be 2.0 to 5.0 μm, 2.0 to 4.5 μm, or 2.0 to 4.0 μm.

[0045] In step b, the closer the true specific gravity of the powder is to the specific gravity of the barium titanate-based compound, the easier it is to obtain the effect of improving the relative dielectric constant by firing. The true specific gravity of the powder used in step b is 5.60 to 5.90 g / cm3 from the viewpoint of making it easier to improve the relative dielectric constant of the obtained barium titanate-based powder. 3 and 5.60 to 5.80 g / cm 3 , 5.65~5.78g / cm 3 or 5.70~5.75g / cm 3 In this specification, the true specific gravity can be measured by Auto True Denser MAT-7000 manufactured by Seishin Enterprise Co., Ltd.

[0046] From the above viewpoint, in step b, the average particle size is 5.0 μm or less, and the true specific gravity is 5.60 to 5.90 g / cm 3 When the above-mentioned collection line is used in the step d, a powder having such an average particle size and true specific gravity can be easily obtained by cyclone collection.

[0047] The average sphericity of the powder used in step b may be greater than 0.80, even greater than or equal to 0.82 or greater than or equal to 0.85. The maximum value of the average sphericity is 1.

[0048] A firing furnace may be used for firing (heating) the powder. The firing temperature of the powder (for example, the temperature in the firing furnace) is, for example, 700°C or higher, and may be 800°C or higher, 900°C or higher, 1000°C or higher, or 1100°C or higher. The higher the firing temperature, the higher the tetragonal crystal ratio tends to be. The firing temperature of the powder is, for example, 1300°C or lower, and from the viewpoint of improving the sphericity, may be 1200°C or lower, 1100°C or lower, or 1000°C or lower. The firing temperature of the powder may be 800 to 1200°C or 900 to 1100°C from the viewpoint of more easily improving the cleaning effect in step c and more easily improving the relative dielectric constant of the barium titanate-based powder. The heating rate of the powder is not particularly limited, and may be 2 to 5°C / min, 2.5 to 4.5°C / min, or 3 to 4°C / min.

[0049] The powder firing time may be 2 hours or more, 4 hours or more, or 6 hours or more from the viewpoint of improving the cleaning effect in step c and the relative dielectric constant of the barium titanate powder. If the powder firing time is 6 hours or more, the tendency of improving the cleaning effect and the relative dielectric constant becomes small, so from the viewpoint of production efficiency, the powder firing time may be 8 hours or less. Note that the firing time does not include the temperature rise time.

[0050] The cooling conditions after firing are not particularly limited. Cooling after firing may be natural cooling in a furnace.

[0051] The fired product obtained in step b is a powder containing barium titanate particles, and has a higher relative dielectric constant than the powder before firing.

[0052] <Process c> In step c, the fired product obtained in step b is washed with an aqueous washing liquid to remove at least a portion of the ionic impurities in the fired product, thereby obtaining a high-purity barium titanate powder.

[0053] The aqueous cleaning liquid contains water as a main component. The content of water in the aqueous cleaning liquid may be 60 to 100 mass%, 70 to 100 mass%, or 80 to 100 mass% based on the total mass of the aqueous cleaning liquid. The aqueous cleaning liquid may consist of only water (e.g., pure water), or may contain other components. Examples of other components include ethanol and acetone.

[0054] The washing is carried out by bringing the fired product into contact with an aqueous washing liquid. Specifically, for example, the fired product can be washed by putting the fired product into the washing liquid and stirring it. In this case, the temperature of the washing liquid may be 10 to 25°C. Stirring can be carried out using, for example, a stirrer, a magnetic stirrer, a disperser, or the like. The stirring time may be 5 to 30 minutes. The stirring speed may be 200 to 400 rpm.

[0055] The amount of the fired product to be brought into contact with the cleaning solution may be 10 to 40 parts by mass, 15 to 35 parts by mass, or 20 to 30 parts by mass, relative to 100 parts by mass of the cleaning solution, from the viewpoint of obtaining a higher cleaning effect. The amount of the fired product is the amount of the fired product to be brought into contact with the cleaning solution per cleaning.

[0056] The washing may be repeated several times. For example, the fired product may be washed by putting the fired product into a washing liquid and stirring the mixture, then the fired product may be allowed to settle, the supernatant liquid may be removed, and the washing liquid may be added again and stirred to wash the fired product. By increasing the number of washings, it is possible to further increase the purity. The number of washings may be two or more, or may be three or more. According to the method of the present embodiment, ionic impurities can be sufficiently removed with a small number of washings, so the number of washings may be 10 or less, or may be 5 or less. The smaller the number of washings, the higher the relative dielectric constant of the obtained barium titanate powder tends to be.

[0057] After washing, the fired product may be dried. The drying conditions may be any conditions that allow the fired product (barium titanate powder) after washing to be sufficiently dried. The drying temperature may be 100 to 110° C. The drying time may be 12 to 24 hours.

[0058] According to the above-described method for producing a barium titanate powder, a barium titanate powder with higher purity can be efficiently obtained. Specifically, a barium titanate powder having a barium ion concentration of 500 mass ppm or less can be obtained. That is, in one embodiment, the present invention provides a barium titanate powder having a barium ion concentration of 500 mass ppm or less. In addition, the extracted water electrical conductivity of the barium titanate powder produced by the above method is, for example, 200 μS / cm or less. That is, in one embodiment, the present invention provides a barium titanate powder having an extracted water electrical conductivity of 200 μS / cm or less (for example, a barium titanate powder having a barium ion concentration of 500 mass ppm or less and an extracted water electrical conductivity of 200 μS / cm or less).

[0059] The barium ion concentration in the barium titanate powder can be reduced by increasing the number of washings. The barium ion concentration in the barium titanate powder can be 480 mass ppm or less, 400 mass ppm or less, 300 mass ppm or less, 200 mass ppm or less, or 150 mass ppm or less. The lower limit of the barium ion concentration in the barium titanate powder is, for example, 130 mass ppm. That is, the barium ion concentration in the barium titanate powder may be 130 to 500 mass ppm, 130 to 480 mass ppm, 130 to 400 mass ppm, 130 to 300 mass ppm, 130 to 200 mass ppm, or 130 to 150 mass ppm.

[0060] The barium ion concentration in the barium titanate powder can be determined by ICP (inductively coupled plasma) emission spectrometry. Specifically, first, 10 g of sample powder (barium titanate powder) is added to 70 mL of ion-exchanged water at 20°C and shaken for 1 minute. Next, the resulting mixture is dried at 95°C for 20 hours. After that, after cooling to room temperature, the evaporated amount of ion-exchanged water is added to the mixture and quantified, then centrifuged, and the supernatant is separated and used as the test liquid. The barium ion concentration is measured by ICP emission spectrometry on this test liquid. Apart from this test liquid, a blank test liquid is prepared by performing the same operation as above except that the sample powder is not used, and the blank test liquid is subjected to the same measurement, and the barium ion concentration can be determined by correcting the measurement result of the test liquid. ICP emission spectrometry can be performed using the "ICPE-9000" manufactured by Shimadzu Corporation.

[0061] The extracted water electrical conductivity of the barium titanate powder can be reduced by increasing the number of washings. The extracted water electrical conductivity of the barium titanate powder can be 100 μS / cm or less, or 70 μS / cm or less. The lower limit of the extracted water electrical conductivity of the barium titanate powder is, for example, 25 μS / cm. That is, the extracted water electrical conductivity of the barium titanate powder may be 25 to 200 μS / cm, 25 to 100 μS / cm, or 25 to 70 μS / cm.

[0062] The electrical conductivity of the extracted water refers to the electrical conductivity of a sample solution (extracted water) prepared by mixing 30 g of barium titanate powder, 142.5 mL of ion-exchanged water with an electrical conductivity of 1 μS / cm or less, and 7.5 mL of ethanol with a purity of 99.5% or more, shaking for 10 minutes, and then leaving the mixture to stand for 30 minutes. The electrical conductivity of the extracted water is the value read after 1 minute of immersing an electrical conductivity cell in the sample solution after standing, and the electrical conductivity of the ion-exchanged water is the value read after 1 minute of immersing an electrical conductivity cell in 150 mL of ion-exchanged water. The electrical conductivity can be measured using an electrical conductivity meter "CM-30R" and an electrical conductivity cell "CT-57101C" manufactured by DKK-TOA Corporation. The shaking in the above extraction operation can be performed using a "Double Action Lab Shaker SRR-2" manufactured by AS ONE Corporation.

[0063] In the above method, the chloride ion concentration of the barium titanate powder can also be reduced. The chloride ion concentration in the barium titanate powder is, for example, 1.5 mass ppm or less, and can also be 1.0 mass ppm or less or 0.9 mass ppm or less. The lower limit of the chloride ion concentration in the barium titanate powder is, for example, 0.7 mass ppm. That is, the chloride ion concentration in the barium titanate powder may be 0.7 to 1.5 mass ppm, 0.7 to 1.0 mass ppm, or 0.7 to 0.9 mass ppm.

[0064] The chloride ion concentration in the barium titanate powder can be determined by IC (ion chromatography). Specifically, a test liquid and a blank test liquid are prepared in the same manner as in the measurement of the barium ion concentration, and IC analysis is performed on them. The chloride ion concentration can be determined by correcting the measurement results of the test liquid using the measurement results of the blank test liquid. IC analysis can be performed using an "INTEGRION" manufactured by Thermo Fisher Scientific Co., Ltd.

[0065] The barium titanate powder obtained by the above method also tends to have an excellent relative dielectric constant. The relative dielectric constant of the barium titanate powder is, for example, 100 or more, and can be 120 or more or 140 or more. The upper limit of the relative dielectric constant of the barium titanate powder is, for example, 310 or less, 250 or less, or 200 or less. That is, the relative dielectric constant of the barium titanate powder may be 100 to 310, 120 to 250, or 140 to 200. The above relative dielectric constant is the relative dielectric constant at 1 GHz, and can be measured using a powder dielectric constant measuring instrument "TM Cavity Resonator" (cylindrical cavity resonance method) manufactured by Keycom Co., Ltd. The measured value is a value corrected by inputting the filling weight and true specific gravity. In addition, when filling the barium titanate powder into the measurement cell, tapping (dropping into the cell) is performed 10 times or more. This sufficiently reduces the porosity, thereby suppressing the variation.

[0066] The barium titanate powder obtained by the above method tends to have high sphericity and high tetragonal crystal ratio. The average sphericity of the barium titanate powder is, for example, 0.80 or more, and can be 0.83 or more, 0.85 or more, 0.87 or more, 0.88 or more, 0.89 or more, or 0.90 or more. The maximum value of the average sphericity is 1, and the above method can obtain a barium titanate powder with an average sphericity close to 1 (for example, 0.80 to 0.99, 0.83 to 0.97, 0.85 to 0.95, 0.87 to 0.93, 0.88 to 0.93, 0.89 to 0.93, or 0.90 to 0.93). The tetragonal crystal ratio of the barium titanate powder is, for example, 65% or more, and can be 68% or more, or 70% or more. The maximum value of the tetragonal crystal ratio is 100%, and the above method can obtain a barium titanate powder with a tetragonal crystal ratio close to 100% (for example, 65 to 95%, 68 to 85%, or 70 to 75%). The tetragonal crystal ratio can be determined by measuring the X-ray diffraction (XRD) pattern of the barium titanate powder using a D2 PHASER manufactured by BRUKER and applying the Rietveld method.

[0067] The average particle size of the barium titanate powder obtained by the above method is, for example, 3.0 to 7.0 μm. The average particle size of the barium titanate powder can be 3.2 μm or more or 3.5 μm or more, and can be 6.5 μm or less, 6.0 μm or less, 5.0 μm or less, 4.5 μm or less, 4.2 μm or less, 4.0 μm or less, or 3.9 μm or less.

[0068] The barium titanate powder obtained by the above method has a high relative dielectric constant, and is therefore suitable for use in various electronic component materials, particularly as a filler for sealing materials that require a high relative dielectric constant. Examples of sealing materials include sealing materials used in antenna-in-packages. When using the barium titanate powder as a filler for sealing materials, it is also possible to use it by mixing it with other filler components. EXAMPLES

[0069] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0070] <Comparative Example 1> (Preparation of ingredients) As a raw material, "BT-SA" (product name, barium titanate powder, average particle size: 1.6 μm) manufactured by Kyoritsu Material Co., Ltd. was prepared and mixed with water to prepare a slurry (BT-SA concentration: 43% by mass).

[0071] (Formation of Barium Titanate Particles) An apparatus was prepared that included a combustion furnace with a double-tube LPG-oxygen mixed burner capable of forming an inner flame and an outer flame installed at the top, a collection line directly connected to the bottom of the combustion furnace, and a blower connected to the collection line. The collection line had a heat exchanger connected to the combustion furnace, a cyclone connected to the top of the heat exchanger, and a bag filter connected to the top of the cyclone, and the bag filter was connected to the blower.

[0072] A high-temperature flame (temperature: about 2000°C) was formed in the combustion furnace of the above equipment, and the above slurry was fed from the center of the burner at a feed rate of 37 L / Hr (25 kg / h in BT-SA equivalent) with carrier air (feed rate: 40 to 45 m 3 The flame was formed by providing several tens of fine holes at the outlet of a double-tube burner, through which LPG (supply rate 17 m 3 / h) and oxygen (supply rate 90m 3 The method was carried out by injecting a mixed gas of barium titanate and argon gas (1000 / h) into the nozzle. This resulted in the formation of spherical barium titanate particles.

[0073] (Classification of powder containing barium titanate particles) The powder containing barium titanate particles formed in the combustion furnace was classified by sucking with a blower, and the powder containing barium titanate particles was collected in each of the combustion furnace, the heat exchanger, the cyclone, and the bag filter. Of the collected powders, the powder collected by cyclone collection was designated as the barium titanate powder of Comparative Example 1.

[0074] <Comparative Example 2> In the same manner as in Comparative Example 1, "formation of barium titanate particles" and "classification of powder containing barium titanate particles" were performed, and then the powder collected by cyclone collection was subjected to a firing treatment. Specifically, 8 kg of the powder collected by cyclone collection was filled into a mullite scabbard, heated to 1000°C at a heating rate of 3.3°C / min, and then fired at 1000°C for 6 hours to obtain barium titanate powder of Comparative Example 2. Note that cooling after firing was performed by natural cooling in a furnace.

[0075] <Examples 1 to 3> As in Comparative Example 1, "formation of barium titanate particles" and "classification of powder containing barium titanate particles" were carried out, and then, as in Comparative Example 2, the powder collected by cyclone collection was subjected to a firing treatment.

[0076] Next, the powder obtained after firing was repeatedly washed with water three, four or ten times. The washing operation consisted of adding 2 L of pure water (20°C) to 500 g of barium titanate powder, stirring at 300 rpm for 10 minutes, leaving it to stand for 30 minutes to allow the powder to settle, and removing the supernatant liquid with a tube pump. After the washing operation was completed, the obtained powder was thoroughly dried at 110°C to obtain barium titanate powders of Examples 1 to 3.

[0077] <Comparative Examples 3 to 5> Similar to Comparative Example 1, "formation of barium titanate particles" and "classification of powder containing barium titanate particles" were performed, and then, similar to Examples 1 to 3, the powder collected by cyclone collection was repeatedly washed with water three, four, or ten times. After completion of the washing operation, the obtained powder was thoroughly dried at 110°C to obtain barium titanate powders of Comparative Examples 3 to 5.

[0078] <Analysis and Evaluation> [Measurement of true specific gravity] The true specific gravity of the barium titanate powders obtained in Comparative Examples 1 to 5 and Examples 1 to 3 was measured using an Auto True Denser MAT-7000 manufactured by Seishin Enterprise Co., Ltd. The results are shown in Table 1.

[0079] [Mean sphericity measurement] The average sphericity of the barium titanate powder obtained in Comparative Examples 1 to 5 and Examples 1 to 3 was measured by the following method. First, the barium titanate powder was mixed with ethanol to prepare a slurry with a barium titanate powder concentration of 1% by mass, and the slurry was dispersed for 2 minutes at output level 8 using a BRANSON SONIFIER450 (crushing horn 3 / 4" solid type). The obtained dispersed slurry was dropped onto a sample stage coated with carbon paste using a dropper. The dropped slurry was left to stand in the air on the sample stage until it dried, and then osmium coating was performed, and the resultant was photographed with a JEOL Ltd. scanning electron microscope JSM-6301F. The photographing was performed at a magnification of 3000 times, and an image with a resolution of 2048 x 1536 pixels was obtained. The obtained image was imported into a photographing computer, and the particles were recognized using an easy import tool using an image analyzer MacView Ver.4 manufactured by Mountec Co., Ltd. From the projected area (A) and perimeter (PM) of a particle, the sphericity of 200 particles with an equivalent circle diameter of 2 μm or more for any projected area was calculated, and the average value was taken as the average sphericity. The results are shown in Table 1.

[0080] [Measurement of average particle size] The average particle size (D50) of the barium titanate powder obtained in Comparative Examples 1 to 5 and Examples 1 to 3 was determined by mass-based particle size measurement by laser diffraction light scattering method using Malvern's "Mastersizer 3000, wet dispersion unit: Hydro MV installed". In the measurement, the barium titanate powder was mixed with water, and the mixture was dispersed for 2 minutes as a pretreatment by applying 200W output using Tommy Seiko's "Ultrasonic Generator UD-200 (with micro tip TP-040 installed)", and the mixture after dispersion treatment was dropped into the dispersion unit so that the laser scattering intensity was 10 to 15%. The stirring speed of the dispersion unit stirrer was 1750 rpm, and there was no ultrasonic mode. The particle size distribution was analyzed by dividing the particle size range of 0.01 to 3500 μm into 100 parts. The refractive index of water was 1.33, and the refractive index of barium titanate was 2.40. The results are shown in Table 1.

[0081] [Measurement of tetragonal crystal ratio] The tetragonal fraction of the barium titanate powders obtained in Comparative Examples 1 to 5 and Examples 1 to 3 was determined by measuring the X-ray diffraction (XRD) patterns of the barium titanate powders using a D2 PHASER manufactured by BRUKER, and by the Rietveld method. The XRD measurement conditions were as follows. The results are shown in Table 1. -Measurement conditions X-ray source: Cu filament (0.4×12 mm 2 ) ·Used output: 30KV-10mA Detector: BRUKER LYNXEYE (1D semiconductor detector) Measurements were performed in the range of 2θ=20°~100° at 0.02° / step and 0.6 sec / step.

[0082] [Measurement of relative dielectric constant] The relative dielectric constant of the barium titanate powders obtained in Comparative Examples 1 to 5 and Examples 1 to 3 was measured using a powder dielectric constant measuring device "TM Cavity Resonator" (cylindrical cavity resonance method) manufactured by Keycom Co., Ltd. The results are shown in Table 1.

[0083] [Measurement of Ba ion concentration and Cl ion concentration] The barium (Ba) ion concentration and chloride (Cl) ion concentration in the barium titanate powder obtained in Comparative Examples 1 to 5 and Examples 1 to 3 were measured by the following method. First, 10 g of barium titanate powder was added to 70 mL of ion-exchanged water at 20°C and shaken for 1 minute. Next, the obtained mixture was placed in a dryer and dried at 95°C for 20 hours. After that, after cooling to room temperature, the evaporated amount of ion-exchanged water was added to the mixture and quantified, then centrifuged, and the supernatant was separated and used as a test liquid. The barium ion concentration and chloride ion concentration were measured for this test liquid by ICP (inductively coupled plasma) emission spectrometry and IC (ion chromatography) analysis. A blank test liquid was prepared separately from this test liquid by the same operation as above except that barium titanate powder was not used, and the blank test liquid was subjected to the same measurement, and the barium ion concentration and chloride ion concentration in the barium titanate powder were obtained by correcting the measurement results of the test liquid. For the ICP emission spectroscopic analysis, an "ICPE-9000" manufactured by Shimadzu Corporation was used, and for the IC analysis, an "INTEGRION" manufactured by Thermo Fisher Scientific Co., Ltd. The results are shown in Table 1.

[0084] [Measurement of electrical conductivity of extracted water] The electric conductivity of the extracted water of the barium titanate powder obtained in Comparative Examples 1 to 5 and Examples 1 to 3 was measured by the following method. First, 30 g of the barium titanate powder was put into a 300 mL polyethylene container, and then 142.5 mL of ion-exchanged water with an electric conductivity of 1 μS / cm or less and 7.5 mL of ethanol with a purity of 99.5% or more were added. Next, the obtained mixed liquid was shaken by a reciprocating shaking method for 10 minutes using a "Double Action Lab Shaker SRR-2" manufactured by AS ONE Corporation, and then left to stand for 30 minutes to prepare a sample liquid (extracted water). An electric conductivity cell was immersed in the sample liquid after standing, and the value was read after 1 minute, and this was used as the electric conductivity of the extracted water. The electric conductivity of the ion-exchanged water was measured by immersing an electric conductivity cell in 150 mL of ion-exchanged water and reading the value after 1 minute. In addition, an electric conductivity meter "CM-30R" and an electric conductivity cell "CT-57101C" manufactured by DKK-TOA Corporation were used to measure the electric conductivity. The results are shown in Table 1.

[0085] [Table 1]

[0086] As shown in Table 1, it was confirmed that in Examples 1 to 3 in which a firing treatment was performed, a barium titanate powder with higher purity was obtained with fewer washing cycles than in Comparative Examples 3 to 5 in which a firing treatment was not performed.

Claims

1. A step a of forming barium titanate particles by injecting a raw material containing barium titanate into a high-temperature field heated to a melting point of barium titanate or higher; A step b of firing the powder containing barium titanate particles formed in the step a; A method for producing a barium titanate powder, comprising: a step c of washing the fired product obtained in the step b with an aqueous washing liquid; The method further includes a step d of classifying the powder containing barium titanate particles formed in the step a to obtain a plurality of powders having different average particle sizes, In the step (b), the powders obtained in the step (d) have an average particle size of 2.0 to 5.0 μm and a true specific gravity of 5.60 to 5.78 g / cm 3 The method for producing a barium titanate powder, wherein the powder containing barium titanate particles formed in the step a is

2. A powder comprising barium titanate particles, The barium ion concentration is 500 ppm by mass or less, When 30 g of the powder, 142.5 mL of ion-exchanged water having an electrical conductivity of 1 μS / cm or less, and 7.5 mL of ethanol having a purity of 99.5% or more are mixed, shaken for 10 minutes, and allowed to stand for 30 minutes to prepare an extract, the electrical conductivity of the extract is 200 μS / cm or less, A barium titanate powder having a relative dielectric constant of 100 to 310 at 1 GHz.

3. The barium titanate powder according to claim 2, having an average particle size of 3.0 to 7.0 μm.

4. The barium titanate powder according to claim 2 or 3, having an average sphericity of 0.80 or more.

5. A filler for an encapsulant comprising the barium titanate powder according to any one of claims 2 to 4.

Citation Information

Patent Citations

  • Resin composition

    JP2003327821A

  • Single crystal ceramic particle and spherical oxide powder

    JP2005112665A

  • Barium titanate powder and its manufacture process

    JP2007261912A

  • Barium titanate fine particle, method for producing the same and multilayer capacitor

    JP2010001180A

  • High-purity barium titanate powder, method for producing same, resin composition, and fingerprint sensor

    WO2017217235A1